Discos sediciosos y volantes prohibidos. La muerte de Obregón entre la censura y el ingenio popular - Díaz Frene, Jaddiel (El Colegio de México, A.C., 2018)
Events such as the assassination of Alvaro Obregon and the trial of Jose de Leon Toral formed part of an extraordinary political process that had a major impact on the everyday life of Mexicans. Instead of reconstructing the history of these events from a political perspective, this article aims to give a history of public opinion and popular culture through media representations that have been little-studied, such as phonographic records and pamphlets. By turning to these sources, this article both gives voice to the lower classes and examines government censorship mechanisms. Legal documents, phonographic records, pamphlets, newspaper testimonies, photographs and plays are all analyzed in the junctures between the printed word and the universe of sound, between subversive writings and the word on the street.